Is Elephant Proof Trench an Effective Mitigating Measure against Human – Elephant Conflict? - Karthick, S.; Ramakrishnan, B. (Indian Forester, 2023)
Human-Elephant Conflict (HEC) is one of the challenging issues posing on elephant conservation. The Elephant Proof Trench is recognized as a potential means of reducing HEC. The effectiveness of EPT in controlling HEC depends on various factors which is not studied so far. This paper describes on effectiveness of EPT in three different geographical landscapes in Tamil Nadu. In a total 470.48 km of EPTes studied in Coimbatore Forest Division, Gudalur Forest Division and Grizzled Giant Squirrel Wildlife Sanctuary altogether. Entire EPT was walked by foot to record wild animal and livestock crossing points. Line transect method was deployed to find out extent of use by wild animals along the EPT and questionnaire method was used to understand people’s perception on EPT. The result revealed that there were 727 animal crossing points and 909 other than animals crossing points. The Elephant (0.63 ER/Km) was frequently used animal. Most of the people (85%) have opined that the maintenance is the duty of forest department. Huge amount being spent for digging EPT every year by the Government is ending with poor result. This present study is envisaged that policy level change is urgently warranted for successful use of EPT grant against HEC.